2021
DOI: 10.3389/fpls.2021.746152
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Root Zone Warming on Maize Seedling Growth and Photosynthetic Characteristics Under Different Phosphorus Levels

Abstract: Phosphorus content and root zone temperature are two major environmental factors affecting maize growth. Both low phosphorus and root zone high temperature stress significantly affect the growth of maize, but the comprehensive effects of phosphorus deficiency and root zone warming are less studied. This study aimed to explore the effects of phosphorus deficiency and root zone warming on the root absorption capacity, total phosphorus content, and photosynthetic fluorescence parameters of maize seedlings. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The plant’s response to temperature changes depends not only on the plant species, but also on the content of nutrients in the soil. According to Xia et al [ 141 ], negative effects of excessive temperature on P content and uptake occur especially in P-poor soils. The authors also found that an overly high root zone temperature reduced root vitality and plant phosphorus content, which in turn affected plant growth and light energy utilization efficiency.…”
Section: Soil Factors Affecting Fuementioning
confidence: 99%
“…The plant’s response to temperature changes depends not only on the plant species, but also on the content of nutrients in the soil. According to Xia et al [ 141 ], negative effects of excessive temperature on P content and uptake occur especially in P-poor soils. The authors also found that an overly high root zone temperature reduced root vitality and plant phosphorus content, which in turn affected plant growth and light energy utilization efficiency.…”
Section: Soil Factors Affecting Fuementioning
confidence: 99%
“…Furthermore, water and P-de ciency alter the activities, morphology and architecture system of the plant roots. Previously, it has been reported that the low phosphorus signi cantly increased the root surface area, root volume and total root length but decreased the average root diameter in maize (Xia et al 2021). Moreover, the maize root surface area and root volume were not affected by drought, but total root length was increased under drought condition (Hussain et al 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Maize (Zea mays L.) is sensitive to drought (Hussain et al 2019, Hussain et al 2020, Shemi et al 2021b) and phosphorus de cit condition (Nadeem et al 2011, Klamer et al 2019, Xia et al 2021) particularly during early growth stages. Single or combined impact of drought and P de ciency considerably decrease maize growth by affecting Fv/Fm, chlorophyll content, leaf relative water content and leaf water potential (Kaya et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The severe environment might weaken P . densiflora seedlings outside patches via suppressing defense systems [ 55 , 58 ], to change the interaction with C . bicorne , which might be not endophytic but weakly pathogenic.…”
Section: Discussionmentioning
confidence: 99%